Psychopathology in adolescent children of physicians. - Stein, B. A. (1984)
The clinical records of 27 adolescent children of physicians who were treated in a psychiatric unit for adolescents were studied. Most of the children had been referred by their physician fathers for evaluation of conduct or mood disorders. These referrals were often the focus of family distress. There appeared to be no typical syndrome presented by physicians' children. Those treating such patients should be especially sensitive to the possibility that parental denial will increase the patient's resistance to therapy. Family therapy, an effective treatment for psychologic problems in adolescents, is often avoided by physicians.